Does sternal body shape reflect family relationships? A study on a genealogically documented Central European osteological sample (19th-20th centuries) - Cvrček, Jan; Kuběna, Aleš Antonín; Jor, Tomáš; Naňka, Ondřej; Drtikolová Kaupová, Sylva; Velemínský, Petr (Anatomical record (Hoboken, N.J., 2023)
In forensic contexts, sternal anatomical varieties represent useful tools for the identification of an individual, either by comparison of ante-mortem and post-mortem data, or by potential comparison of data from biologically related individuals. Sternal body variation is also used to detect the biological affinity of individuals in bioarchaeology. However, no study has been made available to date on the degree to which the overall shape of the sternal body reflects the degree of biological relatedness. We, therefore, analyzed the sternal body shape of 10 individuals with known genealogical data, members of one family over three generations including inbred individuals (19th-20th centuries, Bohemia, Czech Republic), and a control sample of 12 biologically unrelated individuals. First, closely biologically related individuals were compared with unrelated individuals based on 10 variables expressing the morphological characteristics of the sternum, and then all individuals were compared based on Fourier analysis depending on their degree of relationship. The results showed that there is a greater degree of shape similarity in biologically related individuals than in unrelated individuals, and variability decreases with an increasing degree of relatedness. Inbred individuals showed the lowest sternum-shape distances and degree of variability, while unrelated individuals, showed the highest distances and variability. Moreover, in some cases, the documented relationships were also supported by a similar morphology of the ossified and fused xiphoid process. Thus, sternal shape analysis expands the possibilities for individual identification and the detection of the biological affinity of individuals for both the forensic sciences and bioarchaeology.
Keywords: outline; Family Relations; pitva; somatotypy; Fourier analysis; sternum morphology; sternum; Osteogenesis; family; lidé; inbreeding; Somatotypes; Humans; osteogeneze; Autopsy; Sternum; rodinné vztahy